Geologi Daerah Talumolo dan sekitarnya, Kecamatan Dumbo Raya, Provinsi Gorontalo - Alief Ardiansyah; Sri Maryati; Noviar Akase (-, 2026)
This research is located in Talumolo Village and its surroundings in Dumbo Raya District, Gorontalo City, Gorontalo Province, which is located at coordinates 0°32'59" N to 0°34'15" N and 123°02'32" E to 123°04'01" E. This research aims to analyze the geological conditions of the Talumolo area and its surroundings. The methods used include surface geological mapping, lithological analysis, geological structures. The results of the study indicate that the research area is composed of volcanic and sedimentary rocks that have undergone weathering, and has geological structures such as joints and geomorphological conditions of the research area are dominated by denudational hill units and alluvial plain units, which are formed due to weathering and erosion processes over a long period of time.